Assessment of bond strength in CFRP retrofitted beams under marine environment. (15th April 2016) - Subhani, Mahbube; Al-Ameri, Riyadh; Al-Tamimi, Adil
Abstract: Carbon fibre reinforced polymer (CFRP) sheet has gained its popularity to retrofit civil structures which is bonded externally, typically on the soffit of a beam. In this study, the bond between carbon fibre reinforced polymer (CFRP) and concrete is improved by modifying the property of commercial epoxy and compared against normal epoxy. The deterioration in bond strength was produced by placing the beam into salt water under wet dry cycles. Also, a model is proposed to determine the bond strength from flexural test and compared against the available bond strength models which are typically obtained from pull out test. This proposed model shows promising results in terms of predicting the bond strength from flexural test. In addition, a strength reduction factor is introduced to incorporate the effect of wet dry cycles to predict the long term behaviour. It is found that the modified epoxy enhance the ductile property and bond strength.